Embedded microprocessor systems real world design - Ball, Stuart R., 1956- (Amsterdam ; Boston : Newnes, 2002)
The less-experienced engineer will be able to apply Ball's advice to everyday projects and challenges immediately with amazing results. In this new edition, the author has expanded the section on debug to include avoiding common hardware, software and interrupt problems. Other new features include an expanded section on system integration and debug to address the capabilities of more recent emulators and debuggers, a section about combination microcontroller/PLD devices, and expanded information on industry standard embedded platforms. * Covers all 'species' of embedded system chips rather than specific hardware * Learn how to cope with 'real world' problems * Design embedded systems products that are reliable and work in real applications.
System Design; Hardware Design 1; Hardware Design 2; Software Design; Interrupts in Embedded Systems; Adding Debug Hardware and Software; System Integration and Debug; Multiprocessor Systems; Real-Time Operating Systems; Industry-Standard Embedded Platforms; Advanced Microprocessor Concepts; Example System Specifications; Number Systems; Digital Logic Review; Basic Microprocessor Concepts; Embedded Websites.
Includes index.
Keywords: Embedded computer systems -- Design and construction; Microprocessors; Electronic books